Serum Neuroglobin as a Potential Prognostic Biomarker for Cognitive Impairment After Intracerebral Hemorrhage - Gao, Yu; Wang, Bo; Miao, Ye; Han, Yu (Frontiers in Neurology, 2022)
Objective: Stroke is closely related to dementia, but there are few prospective studies on cognitive decline after stroke in patients with cerebral hemorrhage. Neuroglobin is an oxygen-binding protein mainly expressed in brain neurons. The aim of our current study was to determine whether neuroglobin could serve as a biomarker for cognitive prognosis in patients with intracerebral hemorrhage. Methods: 316 patients with ICH were consecutively enrolled in a prospective study. Baseline data such as age and gender of ICH patients on admission were recorded. Serum neuroglobin concentrations were determined by enzyme-linked immunosorbent assay (ELISA). All ICH patients 3 months after onset were divided into post-stroke cognitive impairment group (PSCI) and non-PSCI group according to MoCA assessment results. Results: The PSCI and Non-PSCI groups had serum neuroglobin concentrations of (4.7±0.9) ng/ml and (7.5±1.1) ng/ml, respectively, with a statistically significant difference between the two (p＜0.05). Age, gender, LDL, FBG, SBP, DBP, NHISS, and Hematoma volume were found to be adversely connected with MoCA (p<0.05), while education, HDL, and serum neuroglobin were found to be positively correlated with MoCA (p<0.05). After controlling for baseline data, regression analysis revealed that serum neuroglobin was remained an efficient biomarker for predicting cognitive performance in individuals with ICH (p< 0.05). The diagnostic accuracy of blood neuroglobin concentration for PSCI in ICH patients was 72.6 percent, the sensitivity was 67.4 %, and the specificity was 75.5 %, according to receiver operating characteristic (ROC) curve analysis. Conclusions: Serum neuroglobin may serve as a potential biomarker to predict cognitive decline after intracerebral hemorrhage.